1993
DOI: 10.1172/jci116544
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fatty acid metabolism in familial combined hyperlipidemia. A mechanism associating hepatic apolipoprotein B overproduction and insulin resistance.

Abstract: To establish whether insulin resistance and/or postprandial fatty acid metabolism might contribute to familial combined hyperlipidemia (FCH) we have examined parameters of insulin resistance and lipid metabolism in six FCH kindreds. Probands and relatives (n = 56) were divided into three tertiles on the basis of fasting plasma triglycerides (TG). Individuals in the highest tertile (TG > 2.5 mM; n = 14) were older and had increased body mass index, systolic blood pressure, and fasting plasma insulin concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(89 citation statements)
references
References 49 publications
6
80
0
3
Order By: Relevance
“…40 As reported by other authors, 41 we observed signiÂźcant correlations between hyperinsulinaemia and plasma triglycerides, VLDL-C as well as blood pressure. Hyperinsulinaemia in the basal state has been described as being moderately correlated with concentrations of plasma of apo B and triglycerides.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…40 As reported by other authors, 41 we observed signiÂźcant correlations between hyperinsulinaemia and plasma triglycerides, VLDL-C as well as blood pressure. Hyperinsulinaemia in the basal state has been described as being moderately correlated with concentrations of plasma of apo B and triglycerides.…”
Section: Discussionsupporting
confidence: 75%
“…In the BMI`27 kg/m 2 sub-group, 25% of FCH had basal hyperinsulinaemia compared to 0% in controls; 67.8% had hyperinsulinaemia at 2 h compared to 3.5% in controls; and 28.5% had elevated AUC compared to 3.5% in controls. The observation that hyperinsulinaemia can be present in non obese FCH was also reported by Castro-Cabezas et al 41 On the other hand, obesity aggravates the condition and causes an increase not only of the hyperinsulinaemia but also of blood pressure and glucose intolerance; all of them being acknowledged risk-factors for CVD.…”
Section: Discussionsupporting
confidence: 67%
“…33 Obese women have higher levels of estrogens 37 and are insulin resistant, which together could lead to disturbed postprandial fatty acid handling. Consequently, this may lead to increased postprandial triglyceridemia and an enhanced flux of fatty acids to the liver, promoting the synthesis and secretion of apo B-containing particles 38 and interfering with hepatic uptake of plasma insulin. 39 The TG rich VLDL particles will enter the lipolytic pathway, possibly causing an enhanced escape of non-esterified fatty acids from tissue uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Teleologically, an acute action of insulin on the release of large triglyceride-rich lipoproteins from the liver helps preserve hepatic lipid stores at a time when there is abundant triglyceride present in the circulation in the form of chylomicrons i. e. it is a further 'anabolic' action of the hormone. The impairment of this action in insulin-resistant subjects may be the root cause of their characteristic hypertriglyceridaemia and hence other lipoprotein abnormalities, although increased NEFA transport from adipose tissue to the liver also plays a role [38,39]. The rate of inhibition of VLDL1 apo B release by insulin in normal subjects of 9 % per hour [8] indicates that this phenomenon can contribute to the regulation of triglyceride-rich lipoproteins postprandially.…”
Section: Discussionmentioning
confidence: 99%